2022
DOI: 10.3390/cancers14194870
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Hypoxia-Related Unfolded Protein Response (UPR) in the Tumor Microenvironment

Abstract: Despite our understanding of the unfolded protein response (UPR) pathways, the crosstalk between the UPR and the complex signaling networks that different cancers utilize for cell survival remains to be, in most cases, a difficult research barrier. A major problem is the constant variability of different cancer types and the different stages of cancer as well as the complexity of the tumor microenvironments (TME). This complexity often leads to apparently contradictory results. Furthermore, the majority of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 330 publications
0
15
0
Order By: Relevance
“…Although changing HIF-α isoform dependency during hypoxia has been recognized both in endothelial and cancer cells [ 4 , 17 , 39 , 40 ] as an important regulator of the adaptive response and a potential therapy target, the mechanisms responsible for the hypoxic HIF-1α protein destabilization under low oxygen pressure were less clear. Previous studies in cancer cells have identified hypoxia-associated factor (HAF), that selectively binds and degrades HIF-1α in an oxygen-dependent manner, whereas its binding to HIF-2α selectively increases this factor transactivation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although changing HIF-α isoform dependency during hypoxia has been recognized both in endothelial and cancer cells [ 4 , 17 , 39 , 40 ] as an important regulator of the adaptive response and a potential therapy target, the mechanisms responsible for the hypoxic HIF-1α protein destabilization under low oxygen pressure were less clear. Previous studies in cancer cells have identified hypoxia-associated factor (HAF), that selectively binds and degrades HIF-1α in an oxygen-dependent manner, whereas its binding to HIF-2α selectively increases this factor transactivation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hoechst 33258 staining When ER stress persists, the unfolded protein response is insufficient to remove accumulated unfolded proteins or damaged organelles, and autophagy is activated [29]. When ER stress is too strong or lasts too long, overactivation of autophagy eventually leads to apoptosis [30]. GRP78 overexpression and UPR components have been implicated in the development of malignant gliomas with aggressive phenotypes, whereas ER stress predisposes glioma cells to undergo apoptosis [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Although changing HIF-α isoform dependency during hypoxia has been recognized both in endothelial and cancer cells [4,17,39,40] as an important regulator of the adaptive response and a potential therapy target, the mechanisms responsible for the hypoxic HIF-1α protein destabilization under low oxygen pressure were less clear. Previous studies in cancer cells have identified hypoxia-associated factor (HAF), that selectively binds and degrades HIF-1α in an oxygen-dependent manner, whereas its binding to HIF-2α selectively increases this factor transactivation [41].…”
Section: Discussionmentioning
confidence: 99%